H4SiW12O40 Catalyzed One-Pot Synthesis of 12-Aryl-8,9,10,12-tetrahydrobenzo[a] Xanthen-11-ones Under Solvent-Free Conditions - A. Hassankhani; E. Mosaddegh; S. Y. Ebrahimipour (E-Journal of Chemistry)
An efficient and environmentally benign protocol for the one-pot, three-component synthesis of 12-aryl-8,9,10,12-tetrahydro-benzo[a]xanthen-11-one derivatives by condensation of aryl aldehydes, 2-naphthol and dimedone using H4SiW12O40 (SiWA) as a reusable catalyst with high catalytic activity was reported. The reaction was carried out at 100 ºC under solvent-free conditions within 15-40 min in 82-91% yield.